Investigation of elastic properties of PE/CNT injected composites - Azizi, S.; Fattahi, A. M.; Nel, WAJ (International Journal of Engineering and Technology, 2018)
The aim of this research was to investigate the effect of the addition of carbon nanotubes on the mechanical properties of polyethylene/carbon nanotube nanocomposites. To do so, polyethylene and carbon nanotube were mixed in different weight percentages containing 0, 0.5, 1, and 1.5% carbon nanotube in two screw extruder apparatus by fusion. The effects of carbon nanotube addition in 4 different levels on the tensile strength, elastic modulus and elongation of the nanocomposite samples were investigated. The results showed that the addition of carbon nanotube had a significant effect on improving tensile strength of the nanocomposite samples such that by adding 1% w/w carbon nanotube, the tensile strength 23.4% , elastic modulus 60.4% and elongation 29.7% of the samples improved. Also, according to the results, Manera approximation model at percentages about 0.5% weight and modified Halpin-Tsai at percentages about 1% weight lead to favorite and reliable results.